Membaca Ken Angrok dalam Kacamata Teori Kebenaran - Rohana, Melda Amelia; Putra, Aria; Syaifudin, Syaifudin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Ken Angrok or Sri Ranggah Rajasa Amurwabhumi is one of the famous historical figures during the Hindu-Buddhist kingdom as the founder of the Singhasari or Tumapel kingdom, which was established in 1222. Although his figure is very well-known, the origin and truth of his story cannot be ascertained because no primary source has been found in the form of an inscription issued directly by Ken Angrok. Sources that explain and mention Ken Angrok are non-contemporary sources, namely the Pararaton and Negarakrtagama kakawins, as well as inscriptions from the Wisnuwarddhana era (the fourth king of Singhasari or Tumapel) and inscriptions from the Majapahit era. This article was written to examine the truth of the Ken Angrok figure in history using three theories of truth, namely coherence, correspondence, and pragmatism. The method used in this study is the historical research method, and then analyzed using a descriptive analytical model with an approach to the theory of truth in philosophy. By using this theory of truth, it was concluded that the Ken Angrok figure was a real figure in history, although several things cannot be ascertained due to the lack of supporting sources.